2004
DOI: 10.1017/s109285290000972x
|View full text |Cite
|
Sign up to set email alerts
|

Family Psychoeducation as an Evidence-Based Practice

Abstract: Family psychoeducation programs have emerged as a strongly supported evidence-based practice in the treatment of schizophrenia and bipolar disorder. Over 30 randomized clinical trials demonstrated that psychoeducation programs reduce relapse, improve symptomatic recovery, and enhance psychosocial and family outcomes. Recent work supports family psychoeducation strategies for other disorders, including major depression, obsessive-compulsive disorder, and borderline personality disorder. This review summarizes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 39 publications
1
55
0
6
Order By: Relevance
“…In a large body of randomized trials, FPE programs lasting 9 months or more have demonstrated robust effects in reducing rates of relapse and hospitalization and have also improved social and vocational functioning 59 . A number of meta-analyses 58,60 and literature reviews [59][60][61][62] indicate that FPE is an evidence-based practice. Even more modest levels of family involvement in treatment have been associated with a number of beneficial outcomes, including increased treatment participation 63 ; greater satisfaction with care 64 ; and improved hope, knowledge, and patient empowerment 65 .…”
Section: Results Of Psychoeducational Programsmentioning
confidence: 99%
“…In a large body of randomized trials, FPE programs lasting 9 months or more have demonstrated robust effects in reducing rates of relapse and hospitalization and have also improved social and vocational functioning 59 . A number of meta-analyses 58,60 and literature reviews [59][60][61][62] indicate that FPE is an evidence-based practice. Even more modest levels of family involvement in treatment have been associated with a number of beneficial outcomes, including increased treatment participation 63 ; greater satisfaction with care 64 ; and improved hope, knowledge, and patient empowerment 65 .…”
Section: Results Of Psychoeducational Programsmentioning
confidence: 99%
“…5 Evidence showing benefit for patients with other diagnoses -obsessive compulsive disorder, major depressive disorder, and post-traumatic stress disorderis accumulating. 6 Uganda, a country of 28 million in East Africa, has a psychiatrist: population ratio of 1:1,000,000. 7 It is therefore necessary to use the psychiatrists' expertise to maximum effect while continuing to train other mental health professionals in evidence-based care and exploring creative ways to deliver it.…”
Section: Introductionmentioning
confidence: 99%
“…Considering these findings, authors recommended that family interventions should be offered to families of those with schizophrenia. Several studies and subsequent reviews reported similar results (55,83,92,94,95). Support for family intervention also resulted in some national guideline recommendation that treatment would be offered to caregivers (49,73).…”
Section: Family Interventionsmentioning
confidence: 72%